Thermometric Titration for Rapid Determination of Trace Water in Jet Fuel - Hu, Jian-Qiang; Zhang, Jian-Jian; Yang, Shi-Zhao; Xin, Yong-Liang; Guo, Li; Yao, Ting (Journal of Spectroscopy, 2017)
Water content in jet fuels is detected by thermometric titration (TMT), and the optimal detected system is 2,2-dimethoxypropane as titrant, cyclohexane and isopropanol as titration solvents, and methanesulfonic acid as catalyst in this method. The amounts of oil, concentration and delivery rate of titrant, volumes, and the reliability and accuracy of thermometric titration were emphasized. The results show that the accuracy, validity, and reliability of TMT are excellent by different indicated spiked water contents. The obtained results between TMT and Karl Fischer titration have been proven to be in accord. But, the duration of titration merely spends 3–5 min in the whole process, greatly shortening the detected time. Therefore, rapid and accurate determination of trace water in a jet fuel can be realized by TMT.